Understood and Supported by AI - Månström, Olivia; Nilsson, Tove (My University, 2025)
In moments when institutional support is absent or insufficient, this thesis examines whether AI chatbots can offer meaningful emotional support for people affected by gender inequalities. Focusing on Genie AI, developed at Chalmers University of Technology, we explore users’ emotions when collaborating with two chatbot personalities: one action-driven, the other empathetic. While participants initially expressed a need for concrete advice, their real-time communication with the chatbots said the opposite. Most felt more positively toward the empathic chatbot, suggesting that compassionate presence mattered more than practical guidance. This challenges claims that chatbots should prioritize instrumental support, and instead supports prior research on the value of empathy and human-like traits in chatbots. Finally, the study considers the ethical considerations of designing emotionally attuned chatbots, including risks of bias, manipulation, and misplaced trust. AI will not fix institutional failures, but it might offer something that feels human when it is needed most.
Keywords: Emotional support, AI, Chatbot, User-Centered, Emotions, Anthropomorphism, Human-AI Interaction, Gender Equality, Prompt Engineering, Empathy